2003
DOI: 10.1136/jnnp.74.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Onset age and severity of motor impairment are associated with reduction of myocardial 123I-MIBG uptake in Parkinson's disease

Abstract: Objectives: To elucidate the factors associated with severity of cardiac sympathetic nerve involvement in idiopathic Parkinson's disease (PD). Methods:123 I-metaiodobenzylguanidine uptake was examined in 88 patients with PD. The ratio of the uptake in the heart (H) to that in the mediastinum (M) (the H/M ratio) was calculated and correlated with age at onset, age at examination, and disease severity and duration. Twenty five healthy people were also examined as a control.Results: There was a mild but significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 26 publications
6
44
2
Order By: Relevance
“…This finding was more marked for the delayed compared to the early images ( Figs. 1 and 2), in agreement with several previous studies (4,7,8,(16)(17)(18)(19)(20). The use of 123 I-MIBG has been suggested as a useful marker in the diagnosis of PD (19) and as a sensitive tool in the early detection of silent autonomic dysfunction (18).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This finding was more marked for the delayed compared to the early images ( Figs. 1 and 2), in agreement with several previous studies (4,7,8,(16)(17)(18)(19)(20). The use of 123 I-MIBG has been suggested as a useful marker in the diagnosis of PD (19) and as a sensitive tool in the early detection of silent autonomic dysfunction (18).…”
Section: Discussionsupporting
confidence: 79%
“…1). This finding is in agreement with other studies that reported a decrease in H/M ratio from early and delayed images in normal subjects (17,27,28). Nevertheless, several studies reported a stability or an increase in the H/M ratio over time (1,20,25).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The loss of sympathetic innervation is positively correlated with disease severity (21) and demonstrates a progressive decrease with disease progression (21,27). Although a majority of patients with Parkinson's disease have some degree of sympathetic denervation, not every patient has orthostatic hypotension; however, patients with orthostatic hypotension have a significantly greater sympathetic degree of denervation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although the degree, timing and prognosis of sensory and motor deficits were variable in these reported cases, severe autonomic failure affecting both the sympathetic and parasympathetic functions in the initial phase of the disease was the common feature in these patients. 123 I-meta-iodobenzylguanidine ( 123 I-MIBG) myocardial scintigraphy has been used to examine the function of cardiac sympathetic nerves, particularly the postganglionic fibers (7,8). The beneficial aspects and therapeutic efficacy of 123 I-MIBG myocardial scintigraphy in assessing sympathetic dysfunction have not been described in patients with this type of neuropathy.…”
Section: Introductionmentioning
confidence: 99%